Analisis Penentuan Tarif Jasa Transportasi Udara Rute Kediri - Jakarta di Bandar Udara Kediri - Kurnia Hadi Putra; Fenti Nur Azizah (Jurnal Teknik Sipil, 2021)
Kediri Airport has been developed by Gudang Garam Ltd and Angkasa Pura I Ltd since 15April 2020. This airport will open the access of surrounding areas such as Tulung Agung, Blitar, Ponorogo, Trenggalek, Madiun, and Magetan. To know the tariff value for the flight of Kediri-Jakarta route, the researcher conducted value analyses using ATP (Ability To Pay) and WTP (Willingness To Pay) as well as tariff analysis based on the Government Regulation No.51 Year 2014. Meanwhile, the methods used to count ATP value wasHousehold Budget and the one for calculating WTP wasState Preference.The result of ATP (Ability To Pay) earned averagely IDR 361,000,00, while WTP (Willingness To Pay) gained averagely IDR 784,000,00. This sort of condition was named Captive Riders, meaning that the willingness to pay for transportation service was higher than the ability to pay for transportation service. The calculation using the Government Regulation No. 51 in 2014 obtained tariff IDR 1.204.753,50, in the other words, this value was more than the willingness and ability to pay of passengers who want to use the transport service of Kediri Airport. Accordingly, the subsidy from government is necessary.